The importance of AOP in SOA architecutre - Hołub, Cezary (Znaczenie AOP w architekturze SOA, 2012)
Service oriented architecture (SOA) represents a model to build distributed applications by loosely integrating a number of web services. Aspect-oriented programming (AOP) is a programming paradigm that increases modularity by enabling the improved separation of concerns. Due to the large variety of potential users and the dynamic loosely coupling nature, web services are subject to frequent evolution, which is often required to be done rapidly, and multiple versions may co-exist. In reality it is often the case that existing web services do not perfectly match user requirements in target systems. To achieve the smooth integration and high reusability of web services, mechanisms to support automated evolution of web services in either functional or non- functional aspects are highly in demand. The aim of the paper is underlining the usability of AOP for SOA via theoretical divagation and practical examples in code. We will try to demonstrate the advantages when using the aspect approach in SOA. This article also briefly presented the same concepts of AOP and SOA
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 1 (23), s. 21-37
Keywords: AOP; SOA; Aspect-Oriented Programming; Service-Oriented Architecture; software architecture; programowanie zorientowane aspektowo; architektura zorientowana na usługi; architektura oprogramowania